THE DURABILITY OF RELIGION IN THE SECULAR AGE: RELIGIONIZATION IN INDONESIA - Alamsyah M. Djafar; Unaesah Rahmah (UIN Raden Mas Said Surakarta, 2023)
The global intensification of religionization has raised renewed questions about the validity of the secularization thesis. Research supporting the secularization thesis suggested an alternative perspective, emphasizing the correlation between security levels and religious adherence. It posits that as security levels rise, the reliance on religion diminishes, whereas in contexts of low security, the need for religion intensifies. An examination of the trajectories and dynamics of secularization in Indonesia reveals that among the Muslim middle class, secularization has alleviated feelings of insecurity arising from socio-political crises. Such observations suggest that historical trajectories of religionization are intricately linked to these socio-political dynamics. Furthermore, initiatives by the government and political organizations that endorse religion as a preferred choice expedite this transition towards religionization. This study uses process tracing by dividing the historical process into three periods and comparing them analytically to explain the causal mechanism among modernization, secularization, and religionization.